Pengaruh Efikasi Diri Dan Motivasi Terhadap Pilihan Karir Sebagai Auditor : (Studi Kasus Perguruan Tinggi Negeri Di Jawa Tengah) - Fadila, Apriliya Ayu; Nurcahya, Yulida Army; Panggiarti, Endang Kartini (Politeknik Negeri Ambon, 2024)
This research aims to determine and empirically test the influence of self-efficacy and motivation on the choice as an auditor at state universities in Central Java. This research uses a causality (cause-and-effect) research design. The research method used in this research is a quantitative method with primary data originating from distributing questionnaires via Google Form. The population in this study were active students of the S1 Accounting study program at State Universities in Central Java. The data source in the questionnaire uses a Likert measurement scale ranging from 1-5. The sampling technique for this research was determined by purposive sampling, namely taking samples by considering that the sample selected could represent the population studied. The sample in this study amounted to 262 samples. The sample criteria used in this research are the number of State Universities that open registration for S1 Accounting study programs in Central Java apart from Teaching, students of the 2020 and 2021 S1 Accounting study programs who have taken auditing 1 and auditing 2 courses. Data analysis techniques using multiple linear regression analysis with the SPSS version 25 analysis tool. The results of this research are that self-efficacy variables and motivation variables have a positive and significant effect on the choice as an auditor at State Universities in Central Java.